Analysing the optimum number of cupping points for selected diseases by utilising graph colouring - Aziz, Nur Atikah; Yusof, Yuhani; Mohd Radzuan, Hazulin; Wan Sulaiman, Wan Aliaa; Noviantri, Viska (Semarak Ilmu Publishing, 2025)
An innovative methodology is proposed in optimizing the cupping points related to stroke, insomnia and back pain diseases through the utilization of a graph colouring. Personalized treatment strategies and patient management heavily rely on the optimization of cupping points. By leveraging the powerful tools of graph theory and by the application of colouring approach, this study aims to provide valuable insights into enhancing the optimum number of cupping points for selected diseases. Based on the observations and analysis, shown that the properties of graph colouring hold